ARR1 and AHP interactions in the multi-step phosphorelay system - Tran, Linh H.; Ruszkowski, Milosz (Frontiers in Plant Science, 2025)
Plants use multi-step phosphorelay (MSP) systems in response to exogenous and endogenous stimuli. Cytokinin and ethylene are among the factors that engage MSP signaling cascades but examples independent of phytohormones also exist. The MSP signaling involves four consecutive phosphorylation events at: (i) the kinase domain of the sensory histidine kinase, (ii) the receiver domain of the latter protein, (iii) the histidine-containing phosphotransfer protein, and (iv) the response regulator. In Arabidopsis thaliana, there are eight canonical histidine kinases, five histidine-containing phosphotransfer proteins (AHPs), one pseudo AHP, and 23 response regulators (ARRs). This redundancy suggests complex interactions between signaling pathways, including those involved in phytohormone cross-talk. To bring new insights at the molecular level, we investigated the structural and biophysical characteristics of the AHP1/ARR1 complex. ARR1, a type-B ARR, contains the GARP domain for DNA binding, in addition to the canonical receiver domain that mediates AHP1 interaction. We compared the ARR1 affinities across all five active AHPs and found a modest, two-fold higher affinity for AHP1. This result suggests that while ARR1 shows a slight preference for AHP1, it can also interact with AHP2-5, which potentially makes ARR1 a central node in signaling and a cross-talk modulator. In addition, we discuss the oligomerization state of AHP and related proteins utilizing all available experimental data to conclude that free AHPs are most likely monomeric.